Review of Readiness to Implement Electronic Medical Records in Indonesian Hospitals: Literature Study - Suci Dwi Yanti; Venia Oktafiani; Marlina Gazali; St Kuraedah; Asriani Asriani (International Journal of Science Technology and Health, 2023)
Background: The rapid development of information technology in various sectors has become a common phenomenon in today's digital era. RME is a health information sub-system that is increasingly being adopted in Indonesia and is becoming a global trend in managing documents using computer/electronic based systems in the health sector. One form of progress in information technology in the health sector is the Electronic Medical Record (RME). Research method: The research method uses a literature review design, namely research that has been published. Strategy: using secondary data from the results of research that has been conducted by previous researchers. The source of the data obtained is in the form of articles or journals that are relevant to the topic of readiness to implement electronic medical records. The results of the study: the readiness to implement electronic medical records is still unprepared and some are quite ready. Based on the aspect of human resources it is not quite ready, based on the organizational work culture aspect it is quite ready, based on governance and leadership it is quite ready, and based on infrastructure it is not quite ready.